Self-evaluation of Physical Education Teacher - Muhammad Zulfikar; Abdul Rahman; Andi Hasriadi Hasyim; Haeril Haeril; Faiz Faozi (Journal of Coaching and Sports Science, 2022)
Changes in the level of teacher competency are continually improved through evaluation, ensuring that the learning that is applied to students remains innovative. The goal of this study was to discover physical education teachers' self-evaluation of teaching effectiveness. This study is descriptive that employs the survey approach. Fifty-one elementary school physical education teachers in South Sulawesi Province (aged 20 to 58 years) volunteered to participate in this study. The Self-Evaluation of Teacher Effectiveness Questionnaire in Physical Education (SETEQ-PE) was utilized in this study to assess teacher effectiveness in teaching physical education. This efficacy is measured using six components: learning environment, teacher and student evaluation, application of learning content, use of technology, teaching methodologies, and lesson execution. The findings revealed that the overall average physical education teachers' teaching effectiveness score was in the high range (140). In terms of gender, male instructors have a high average score (139.5), whereas female teachers have a very high average score (139.5). (142). Even though female teachers have a higher score than male teachers, there is no significant difference in their scores, with a significance value of 0.731. Given the small sample size of this study, additional research should be undertaken on a broader scale to investigate other aspects that may influence teaching effectiveness.